Mixed-Member Electoral Systems in Constitutional Context - Batto, Nathan F.; Huang, Chi; Tan, Tan C.; Cox, Gary W. (University of Michigan Press, 2021)
"Reformers have promoted mixed-member electoral systems as the “best of both worlds.” In this volume, internationally recognized political scientists evaluate the ways in which the introduction of a mixed-member electoral system affects the configuration of political parties. The contributors examine several political phenomena, including cabinet post allocation, nominations, preelectoral coalitions, split-ticket voting, and the size of party systems and faction systems. Significantly, they also consider various ways in which the constitutional system—especially whether the head of government is elected directly or indirectly—can modify the incentives created by the electoral system.